Integrating Communicative Language Teaching to Enhance Speaking Competence Among Pre-Service English Teachers: A Quasi-Experimental Study - Safitri, Ana (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
This study investigates the effectiveness of integrating Communicative Language Teaching (CLT) in enhancing speaking competence among pre-service English teachers at the tertiary level. Employing a quasi-experimental design with a pretest–posttest control group, the study involved 60 third-semester students enrolled in a Speaking for Academic Purposes course. The experimental group received instruction through CLT-based communicative tasks, while the control group was taught using conventional lecture-based instruction. Data were collected through a performance-based speaking test assessed using an analytic rubric covering fluency, grammatical accuracy, vocabulary range, pronunciation, and interactive communication. Statistical analyses using paired-sample and independent-sample t-tests revealed a statistically significant improvement in the experimental group compared to the control group (p < .05). The findings indicate that CLT fosters meaningful interaction, increases learner autonomy, and significantly improves communicative competence. The study recommends systematic CLT integration in English teacher education programs to better prepare future educators for communicative classroom contexts.